PENGELOLAAN KEBUN KARET RAKYAT DI AREA TRANSISI CAGAR BIOSFER GIAM SIAK KECILâBUKIT BATU - , ZAWIL HIJRI, Prof. Dr. Ir. San Afri Awang. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Objectives of this research were : (1) to describe the management process of community rubber plantations in Giam Siak Kecil-Bukit Batu (GSK-BB) Reserve Transition Area, (2) to describe the economic benefit of community rubber plantation in GSK-BB Biosphere Reserve Transition Area, (3) to compare the vegetation biodiversity of community rubber plantations among several locations in GSK-BB Biosphere Reserve Transition Area. Location of this research was in Temiang village, Bukit Batu sub district, Bengkalis district, Riau Province. This study used survey method (for objectives 1 and 2) and biodiversity measurement (for objective 3). Survey was conducted by interviewing 30 respondents, whereas biodiversity measurement was collected from 20mx20m quadrat of measuring plots in 9 locations of rubber plantations. The results of this study were: (1a) most of the rubber plantation management process was conducted by following stages: slashing, making firebreaks, burning, rubber planting which started by rice planting, weeding periodically by herbicides, tapping which conducted in the morning and selling to intermediate traders